2010
DOI: 10.1007/s10157-010-0376-y
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation-associated thrombotic microangiopathy after steroid pulse therapy for polyserositis related to graft-versus-host disease

Abstract: Transplantation-associated thrombotic microangiopathy (TA-TMA) is a rare but devastating syndrome that occurs in allogeneic hematopoietic stem cell transplant recipients, and is associated with a variety of transplantation-related factors, including conditioning regimens, immunosuppressive agents, graft-versus-host disease (GVHD) and opportunistic infections. TA-TMA has an unfavorable prognosis and responds poorly to conventional treatment including plasma exchange (PE). We present a case of a 37-year-old man … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Traditionally, significant cardiac and pulmonary vascular endothelial toxicities after HSCT were attributed to chronic GVHD or chemotherapy and radiation effects [66,67]. However, polyserositis has been described in TA-TMA, presenting as refractory pericardial effusion, pleural effusion, and ascites without overall generalized edema [49].…”
Section: Serosal Surfacesmentioning
confidence: 99%
“…Traditionally, significant cardiac and pulmonary vascular endothelial toxicities after HSCT were attributed to chronic GVHD or chemotherapy and radiation effects [66,67]. However, polyserositis has been described in TA-TMA, presenting as refractory pericardial effusion, pleural effusion, and ascites without overall generalized edema [49].…”
Section: Serosal Surfacesmentioning
confidence: 99%
“…It often presents as refractory pericardial effusion, pleural effusion, and ascites without overall generalized edema even in patients with nephrotic range protein-uria. Polyserositis after allogeneic HSCT is often thought to be a presentation of chronic GVHD [15,49]. TA-TMA should be included in the differential diagnosis, especially in patients who do not exhibit other symptoms of GVHD, like chronic skin or mucosal changes and in patients with polyserositis after autologous HSCT.…”
Section: Clinical and Histologic Featuresmentioning
confidence: 99%
“…Ishikawa et al [2] reported a case of polyserositis as an isolated finding of cGVHD 21 months after bone marrow transplant (BMT) and 4 months after developing skin GVHD. In our cases, the effusions occurred before day +100, without acute GVHD.…”
Section: Discussionmentioning
confidence: 99%